Twenty years of monitoring of persistent organic pollutants in Greenland biota. A review. (October 2016) - Rigét, F.; Vorkamp, K.; Bossi, R.; Sonne, C.; Letcher, R.J.; Dietz, R.
Abstract: The Arctic Monitoring and Assessment Programme (AMAP) is a working group under the Arctic Council with the aim to monitor and assess temporal trends of contaminants in Arctic ecosystems. The Greenland AMAP Core programme was established to contribute to this effort. The Core programme includes three main components; routine monitoring, retrospective studies and new POP screening studies. The programme is based on an adaptive approach, which has led to changes throughout the years. An overview of the temporal trends during the last two to three decades is presently given together with selected examples of different characteristic trends of POPs. The results show how tissue banked samples and retrospective studies has helped in establishing time-series of compounds of emerging concern. Lastly, the statistical power of the Greenlandic time-series is discussed. The lesson learned is that trend monitoring improves with samples over time, and only pays off after decades of data are generated. Graphical abstract: Abstract : The lessons learned by twenty years of monitoring POP in Greenland biota.